A Novel Membraneless Direct Hydrazine/Air Fuel Cell. Issue 6 (8th October 2014) - Yi, Q.; Chu, H.; Tang, M.; Zhang, Y.; Liu, X.; Zhou, Z.; Nie, H.
Abstract In this paper multi‐walled carbon nanotubes (MWCNTs) supported binary AgNi nanoparticles are prepared by chemical reduction of Ag and Ni precursors with NaBH4. Fe/PANI catalyst is obtained by direct pyrolysis of Fe‐doped polyaniline in N2 atmosphere at high temperature. Results show that the Fe/PANI catalyst presents high electroactivity for oxygen reduction reaction (ORR) in alkaline media. The onset potential for ORR is 0.01 V(vs Hg/HgO) and the ORR current density is 3.4 mA cm−2@2000rpm at –0.4 V(vs HgO/Hg). A gas diffusion electrode is fabricated by using the Fe/PANI as the electrocatalyst of ORR. In alkaline media the AgNi/MWCNT catalyst displays efficient electroactivity for hydrazine oxidation. A lower onset potential of –0.5 V(vs Hg/HgO) and high current density for hydrazine oxidation are observed. A novel membrane‐less direct hydrazine/air fuel cell is designed by using the AgNi/MWCNT catalyst as the anode and the gas diffusion electrode as the cathode. The as‐fabricated fuel cell works properly and presents higher power density and current density.